2019
DOI: 10.14720/aas.2019.114.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Biochar application in alkaline soil and its effect on soil and plant

Abstract: <p>Scientists reported that biochar can improve soil properties in acidic soils, while in alkaline soils were shown negative results. A field study was done to evaluate the effect of biochar application solely in alkaline soil compared with biochar composts with farm yard manure (BC-FYM) and sulfur (BC-S). The results revealed that using solely biochar decreased yield of potatoes tubers to more than 6 % and 10 % using mineral and organic fertilization, respectively. This was attributed to the alkalinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
(59 reference statements)
1
5
0
Order By: Relevance
“…These relationships were statistically reinforced by PCA, which showed two very different groupings, corresponding, on the one hand, to the blockage of Pi through micronutrients bridges and, on the other hand, the potential liming action of Ca and Mg ( Figure S6). These relationships were supported by the results obtained in the greenhouse experiment with tomato ( Figure S7), which showed positive results in acidic soils, but any effect in the alkaline soils agreed with the results reported by other studies [2,8] (Figure 5). It is noteworthy that the result obtained for N foliar content in acidic soil increased with biochar treatment ( Figure 6).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These relationships were statistically reinforced by PCA, which showed two very different groupings, corresponding, on the one hand, to the blockage of Pi through micronutrients bridges and, on the other hand, the potential liming action of Ca and Mg ( Figure S6). These relationships were supported by the results obtained in the greenhouse experiment with tomato ( Figure S7), which showed positive results in acidic soils, but any effect in the alkaline soils agreed with the results reported by other studies [2,8] (Figure 5). It is noteworthy that the result obtained for N foliar content in acidic soil increased with biochar treatment ( Figure 6).…”
Section: Discussionsupporting
confidence: 90%
“…A possible strategy to resolve the possible blockage of micronutrients and Pi in soils might be the use of humified organic matter mixed with biochar, as proposed by some authors [8,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BC40%+Urea60%, consisting of both biochar and chemical fertilizer, had a positive effect through the synergistic effect of biochar and chemical fertilizer for nutrients (Schulz and Glaser, 2012), nitrogen availability, and the ability for water as well as nutrient availability and retention (Herlihy and Carroll, 1969;Youseef et al, 2017). The negative impact of sole biochar application on production could be attributed to the alkalinity effect of biochar, raising pH, in turn, reducing nutrient availability (Salem et al, 2019), N immobilization, and the probable presence of inherent undesirable compounds (Lehmann and Joseph, 2015;Solaiman et al, 2012;Spokas et al, 2012). Higher dry matter as produced by BC40%+Urea60% could be attributed to its role in tuber maturity, growth characters (leaves, canopy, stem), water and nutrient uptake (Gebre et al, 2020;Youseef et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of biochar application on the properties of alkaline soils with high pH and CaCO 3 values are not well understood and have received much less attention. Previous studies have reported contrasting effects of biochar addition on soil and plants in alkaline soil [17–19].…”
Section: Introductionmentioning
confidence: 99%